Solving the fever mystery: Fever and tonsillar ulcer in an elderly patient - Jasmine Shimin Chung; Zhentang Lao; Ban Hock Tan (Proceedings of Singapore Healthcare, 2015)
Pyrexia of unknown origin in the elderly is not an uncommon clinical problem. In day to day clinical practice, it has been observed that antibiotics are often empirically escalated to ‘treat fever’ in an otherwise well patient. However, this may not be warranted. It is more important that a comprehensive history, detailed physical examination and a systematic evaluation be undertaken to identify the cause so that definitive therapy may be administered. Apart from infection, neoplastic and connective tissue disorders are other common causes of pyrexia of unknown origin which should be considered. We describe our approach for evaluating an 80-year-old man who presented with fever and sore throat.